Aberrant expression of transglutaminase 2 in pancreas and thymus of NOD mice underscores the importance of deamidation in neoantigen generation - Callebaut, Aїsha; Bruggeman, Ylke; Zamit, Cloé; Sodré, Fernanda Marques Câmara; Irla, Magali; Mathieu, Chantal; Buitinga, Mijke; Overbergh, Lut (Frontiers in Endocrinology, 2022)
Post-translational modifications can lead to a break in immune tolerance in autoimmune diseases such as type 1 diabetes (T1D). Deamidation, the conversion of glutamine to glutamic acid by transglutaminase (TGM) enzymes, is a post-translational modification of interest, with deamidated peptides being reported as autoantigens in T1D. However, little against deamidated peptides is lost. Here, we report on the aberrant expression and regulation of Tgm2, in the pancreas and thymus of NOD mice. We demonstrate that Tgm2 expression is induced by the inflammatory cytokines IL1β and IFNγ in a synergistic manner and that murine pancreatic islets of NOD mice have higher Tgm2 levels, while Tgm2 levels in thymic mTECs are reduced. We thus provide the first direct evidence to our knowledge that central tolerance establishment against deamidated peptides might be impaired due to lower Tgm2 expression in NOD mice, which together with the aberrantly high levels of deamidated peptides in NOD β-cells underscores the role of deamidation in amplifying T-cell reactivity.